Analisis Efektivitas Pelaksanaan Penghapusan Sanksi Administrasi Pajak Hotel Dalam Rangka Pemulihan Ekonomi Di Kota Jakarta Pusat Pada Masa Pandemi Covid – 19 Tahun 2021 - Azzyyati Inggita Caestyakara; Rahadi Pratomo Singgih (Jurnal Ilmu Administrasi Publik, 2022)
A regional tax is a kind of tax that is collected and managed by the regional government and is used for funding all governmental functions and regional development. Regional Income Board is a Regional board assigned to manage all types of regional receivables and income, one of which is Hotel Tax. This study was conducted to find out how the Effectiveness of Hotel Tax Administration Penalty Removal that is regulated in Governor Regulation Number 60 of 2021 in Regional Income Board of (Central) Jakarta in order to increase economic recovery in Jakarta central city in Covid-19 pandemic era. This study uses a descriptive qualitative research method. Data collected was conducted through an interview, observation, and documentation. The result of this study presented that the effectiveness of the hotel tax administration penalty removal in the Covid-19 pandemic era is very effectiveif it is assessed from the hotel tax receivable target and realization. However, it has not yet been maximized in the implementation. The lack of maximizing in the hotel taxpenalty removal in order to recover economics is due to several obstacles, such as people's knowledge of this governor's regulation